أثر برنامج قائم على عادات العقل في تحسين بعض المشكلات السلوكية لدى تلاميذ المرحلة الابتدائية ذوي صعوبات التعلم الاجتماعية والانفعالية - عبدالساتر، علا سيد; كامل، عاصم عبدالمجيد; بدوي، منى حسن السيد (الأكاديمية العربية للعلوم الإنسانية والتطبيقية, 2021)
تتحدد مشكلة الدراسة الراهنة من خلال ما لاحظته الباحثة من خلال العمل في مجال التربية الخاصة بالمركز القومي للبحوث أن هناك فئة من التلاميذ لا يعانون من أي إعاقات عقلية أو جسدية حيث تراوحت درجات ذكاءهم ما بين (٩٠-١١٠) ويشكو الآباء من بعض المشكلات السلوكية والانفعالية مثال (العدوان - انسحاب اجتماعي - عدم الثقة بالنفس) وعدم القدرة على مواكبة من هم في مثل أعمارهم وكذلك نتائج الدراسات والبحوث التي أشارت إلى وجود مشكلات سلوكية وانفعالية لدى هؤلاء التلاميذ مثل دراسة، توجيه التربويين إلي أهمية تحسين جودة الحياة من أجل التعامل الكفء مع ظروف الحياة المحيطة خاصة مع التلاميذ ذوي صعوبات التعلم الاجتماعية والانفعالية، إلقاء الضوء علي المشكلات السلوكية التي يعاني منها التلاميذ ذوي صعوبات التعلم الاجتماعية والانفعالية. تحسين جودة الحياة وخفض بعض المشكلات لدى تلاميذ ذوي الصعوبات الاجتماعية والانفعالية. استفادة أولياء الأمور وثقل خبرتهم للتعامل مع أبنائهم من ذوي الصعوبات الاجتماعية والانفعالية. استفادة المعلمين وتزويدهم بخبرات في كيفية التعامل مع التلاميذ ذوي صعوبات التعلم الاجتماعية والانفعالية. مساعدة التلاميذ ذوي صعوبات التعلم الاجتماعية والانفعالية على التكيف مع زملاءهم وإكسابهم عادات عقل جديدة تساعدهم في حل المشكلات.
The problem of the current study is determined by what the researcher noticed through working in the field of special education at the National Research Center that there is a group of students who do not suffer from any mental or physical disabilities, as their intelligence degrees ranged between (90-110) and parents complain about some behavioral and emotional problems Example (aggression - social withdrawal - lack of self- confidence) and the inability to keep pace with those of their age, as well as the results of studies and research that indicated the existence of behavioral and emotional problems among these students, such as studying, directing educators to the importance of improving the quality of life in order to deal efficiently with the conditions Surrounding life, especially with students with social and emotional learning difficulties, shedding light on the behavioral problems that students with social and emotional learning difficulties suffer from. Improving the quality of life and reducing some problems for students with social and emotional difficulties. Benefiting from parents and the weight of their experience to deal with their children with difficulties. Social and emotional. Benefiting teachers and providing them with experiences in how to deal with students with social and emotional learning difficulties. Students with social and emotional learning disabilities have to adapt with their colleagues and acquire new habits of mind that help them solve problems.
Keywords: طلبة المرحلة الابتدائية -- صعوبات التعلم الاجتماعية والانفعالية -- المشكلات السلوكية -- عادات العقل -- التربية الخاصة